2010
DOI: 10.1371/journal.pone.0014260
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Key Tinnitus-Related Brain Regions Documented by a Unique Combination of Manganese-Enhanced MRI and Acoustic Startle Reflex Testing

Abstract: Animal models continue to improve our understanding of tinnitus pathogenesis and aid in development of new treatments. However, there are no diagnostic biomarkers for tinnitus-related pathophysiology for use in awake, freely moving animals. To address this disparity, two complementary methods were combined to examine reliable tinnitus models (rats repeatedly administered salicylate or exposed to a single noise event): inhibition of acoustic startle and manganese-enhanced MRI. Salicylate-induced tinnitus result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 68 publications
7
92
0
1
Order By: Relevance
“…Isoflurane also significantly reduced this startle response amplitude in 5/10 animals. Increased startle response amplitudes following a tinnitus inducer (such as acoustic trauma or salicylate) are consistent with previous studies, and have been suggested as a possible behavioral correlate of hyperacusis (Ison et al, 2007;Holt et al, 2010;Turner and Parrish, 2008;Sun et al, 2009).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Isoflurane also significantly reduced this startle response amplitude in 5/10 animals. Increased startle response amplitudes following a tinnitus inducer (such as acoustic trauma or salicylate) are consistent with previous studies, and have been suggested as a possible behavioral correlate of hyperacusis (Ison et al, 2007;Holt et al, 2010;Turner and Parrish, 2008;Sun et al, 2009).…”
Section: Resultssupporting
confidence: 90%
“…The reversibility of temporary tinnitus offers practical experimental advantages, such as the ability to compare brain activity when the animal is or is not experiencing tinnitus. For example, temporary tinnitus produced by high doses of salicylate alters both driven and spontaneous activity levels and inhibitory function at multiple levels of the auditory system, including dorsal cochlear nucleus, inferior colliculus, and auditory cortex (Bauer et al, 2000;Holt et al, 2010;Ralli et al, 2010;Stolzberg et al, 2011;Zhang et al, 2011). However, because drug-induced tinnitus and noise-induced tinnitus may arise from distinct brain mechanisms (Eggermont, 2008;Sun et al, 2009;Norena et al, 2010), a method for inducing temporary noiseinduced tinnitus is likely to be useful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…System-level tinnitus alterations have been extensively investigated in the dorsal cochlear nucleus (DCN) (Kaltenbach, 2006; Kaltenbach et al, 2008), inferior colliculus (Bauer et al, 2008; Holt et al, 2010; Jastreboff et al, 1986; Melcher et al, 2000), auditory thalamus (Kalappa et al, 2014; Richardson et al, 2011), and auditory cortex (Deng et al, 2015; Engineer et al, 2011; Langers et al, 2012; Norena et al, 2006; Tan et al, 2007; Zhang et al, 2011). Nevertheless specific cellular mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following the hypothesis that subcortical hyperactivity during tinnitus may occur in the DCN independently of the cochlea (Kaltenbach, 2011 ) , a selective activation of nonlemniscal pathways may be a likely consequence. This would explain recent fi ndings of hyperactivity in the dorsal cortex of the inferior colliculus (DCIC) rather than in the central nucleus of the inferior colliculus (CIC) (Holt et al, 2010 ) . The major sources of input to the dorsal part of the MGB are from nonlemniscal parts of the IC, the DCIC and external cortex of the inferior colliculus (ECIC) that in turn receive ascending information from the (dorsal nucleus of the lateral lemniscus [DNLL]) (Malmierca & Merchán, 2004 ) .…”
Section: Molecular Aspects At the Level Of Limbic And Paralimbic Strumentioning
confidence: 92%